Acid corrosion inhibition of copper by mangrove tannin - Shah, A.M.; Rahim, A.A.; Yahya, S.; Raja, P.B.; Abd Hamid, Shafida (Emerald Group Publishing Limited, 2011)
Purpose – The purpose of this paper is to evaluate the corrosion inhibition potential of mangrove (Rhizopora apiculata) tannin in hydrochloric acid medium on copper with the view of developing a natural corrosion inhibitor.